HOMESCHOOLING AS VEHICLE CHARACTER DEVELOPMENT : Case Studies In Homeschooling KakSeto in Cirebon West Java - Istar, Lusy Febia Yaomul (2013)
One of the goals of education is to make students siswinya to have good character, of course, various ways and measures implemented by steakholder education, such as the one made by the parents to always supervise their child behavioral development so that no part by the negative things like fighting, drugs, smoking, sec-free, and others. In the community even today continues to develop innovations in education to support the existence of homeschooling institutions with the aim of creating young people who have good character, which one day will bring the nation to be better and evolve. In line with this, homeschooling KakSeto develop character building in each process of learning and the implementation of all activities of homeschooling. This research seeks revealed some formulation of the problem, namely: (1) How does the process of character building for students in homeschooling KakSeto in Cirebon West Java, (2) What are the values of the characters are developed in homeschooling KakSeto in Cirebon West Java, (3) What obstacles encountered in the process of building character in students in homeschooling KakSeto in Cirebon West Java, (4) What are the efforts made to overcome the obstacles that exist in homeschooling KakSeto in Cirebon West Java in the development of character in students. The approach used is to use a qualitative approach, and the method used is a case study. Collection of data obtained through interviews, observation (observation), study documentation, field notes and literature. Locations used in this study is homeschooling KakSeto, the Institute of homeschooling. The results showed that: (1) The process of character building of the students in homeschooling is done through Civic Education subjects and other subjects, and other activities of the project through class, distance learning, gathering, outing, and refreshing study. (2) The values of the characters are developed in homeschooling can be categorized into two sub-orientation of the applicative value, namely: a) the value of self-orientation, include: self-reliance, responsibility, tolerance, besosialisasi, etc., b) value orientation toward others and communities, include: being able to socialize, mutual cooperation, mutual respect and appreciation, etc..(3) Obstacles encountered include: feeling lazy and bored while studying, lack of friends on homeschooling, limited facilities and infrastructure, lack of professional teachers, constraint when calling or inviting parents, (4) Efforts made in overcoming obstacles there are: hold refreshing and the specific approach (face to face) that teachers and parents, gathered with friends outside of homeschooling.